Digitalisasi Ekonomi Sebagai Upaya Peningkatan Omzet UMKM di Sentra Industri Kasongan - Ratnadewati, Ainina; Widiastuti, Nur; Noviana, Dian (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2023)
This research aims to determine the impact the digital economy which includes gadget ownership, internet use, marketing through E-commerce, and advertising through social media on MSME turnover in the Kasongan Craft Industry Center. The data used are cross- sectional data, the independent variables are: possession of gadgets; and internet usage Internet use consists of: marketing through E-commerce and advertising through social media; while the dependent variable used is MSME turnover. This study uses primary data obtained from 30 samples of MSMEs at the Kasongan Handicraft Industry Center, Bantul Regency. The method used is multiple linear regression using the EVIEWS 10 application. All independent variabel affect dependen variabel. Aspects of the digital economy that affect MSME turnover in the Kasongan Industrial Center, Bantul Regency, namely: gadget ownership, internet use, and advertising through social media. Product marketing through E-commerce has no effect on turnover. This influence indicates that the majority of MSMEs in these centers have implemented the digital economy as a means to market their products. As a result, the marketing of these products increases turnover so that market penetration efforts also increase.